Functional assessment of the reconstructed urinary tract. Issue 3 (May 2017) - Wood, Dan
Abstract : Reconstruction of the urinary tract is increasingly advanced. However, we need to be able to follow up patients with the appropriate parameters to make sure surgery is successful in the short, medium and long term. This article aims to consider these parameters and the framework by which the reconstructed urinary tract can be assessed.